2019
DOI: 10.1038/s41598-019-53716-y
|View full text |Cite|
|
Sign up to set email alerts
|

Air pollution-derived particulate matter dysregulates hepatic Krebs cycle, glucose and lipid metabolism in mice

Abstract: Exposure to ambient air particulate matter (PM2.5) is well established as a risk factor for cardiovascular and pulmonary disease. Both epidemiologic and controlled exposure studies in humans and animals have demonstrated an association between air pollution exposure and metabolic disorders such as diabetes. Given the central role of the liver in peripheral glucose homeostasis, we exposed mice to filtered air or PM2.5 for 16 weeks and examined its effect on hepatic metabolic pathways using stable isotope resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 79 publications
(89 reference statements)
2
22
0
Order By: Relevance
“… 183 Although not completely understood, individual and time‐dependent doses influence the mechanisms by which environmental air pollutants result in cancer cell transformation. The impact of air pollution particular carcinogens and their mixtures disrupt several molecular processes through direct or indirect (inflammation and oxidative stress) damage, inducing TSG inactivation and the activation of oncogenes, 184 cell cycle alterations dependent on TP53 activation, 185 activation of energetic dysregulation, 186 chromosome instability, 187,188 the inhibition of apoptosis, 189 and the induction of cell proliferation in somatic cells 190 . Further research will clarify which mechanisms are most relevant and can be used as early biomarkers of air pollution‐related cancer.…”
Section: Biological Mechanisms Of Air Pollution‐derived Carcinogenesismentioning
confidence: 99%
“… 183 Although not completely understood, individual and time‐dependent doses influence the mechanisms by which environmental air pollutants result in cancer cell transformation. The impact of air pollution particular carcinogens and their mixtures disrupt several molecular processes through direct or indirect (inflammation and oxidative stress) damage, inducing TSG inactivation and the activation of oncogenes, 184 cell cycle alterations dependent on TP53 activation, 185 activation of energetic dysregulation, 186 chromosome instability, 187,188 the inhibition of apoptosis, 189 and the induction of cell proliferation in somatic cells 190 . Further research will clarify which mechanisms are most relevant and can be used as early biomarkers of air pollution‐related cancer.…”
Section: Biological Mechanisms Of Air Pollution‐derived Carcinogenesismentioning
confidence: 99%
“…Hepatocytes can directly clear LPS from the bloodstream through hepatic uptake via TLR4, indicating their important role in in ammatory responses 33 . Both epidemiologic and controlled exposure studies in humans and animals have demonstrated an association between air pollution exposure and metabolic disorders such as diabetes 34 . It was also found that IL-6 levels were elevated in blood, liver, adipose tissue, and macrophages, which induced activation of the STAT3/SOCS3 pathway in liver 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This has been associated with higher oxidative stress and toxicity compared to other sources [ 34 , 36 ]. Oxidative stress may be involved in all PM-induced disorders in multiple organ systems, including the lung, cardiovascular system and liver, which activate the endogenous redox system [ 37 , 38 , 39 , 40 ].…”
Section: Particulate Matter (Pm)—an Intrauterine Toxinmentioning
confidence: 99%